Evaluation of maternal immune activation with post-weaning social isolation as a potential rat model for schizophrenia - Goh, Jen-Yin (2020)
Schizophrenia is a disabling neurodevelopmental disorder whose risk factors are diverse, aetiology is unclear and symptoms remain inadequately treated. The development of animal models with improved face, construct and predictive validity would facilitate our understanding of its neurobiology, and aid development of novel therapeutics. In this thesis, the combination of maternal immune activation (MIA) in pregnant dams and post-weaning social isolation (SI) of resultant rat offspring is evaluated to determine whether this ‘dual-hit’ neurodevelopmental model produces a more comprehensive array of behavioural and neurochemical changes akin to those observed in schizophrenia than either intervention alone. At gestational day (GD) 15, pregnant dams received a single intraperitoneal (i.p., 10 mg kg-1) or intravenous (i.v., 6 mg kg-1) injection of a viral mimetic, polyinosinic:polycytidylic acid (poly(I:C)), or vehicle saline (1 ml kg-1). Resultant offspring were housed in groups or alone (in isolation) from weaning. In adulthood, male offspring underwent comprehensive behavioural analysis using paradigms relevant to the positive, negative and multiple cognitive domains of schizophrenia and potential mechanisms underlying behavioural abnormalities were studied. Regardless of route of administration, poly(I:C) alone had relatively subtle effects. Interestingly, i.p. poly(I:C) conferred an unexpected resilience towards SI-induced behavioural (locomotion, aggressive behaviour and conditioned fear) and immune abnormalities. Investigations into potential early molecular mechanisms showed a sophisticated interplay between stress experience and gender on long-term behavioural and immune outcomes. When combined with SI, i.v. poly(I:C) resulted in some additive effects on certain behavioural measures related to the positive, negative and cognitive symptoms (locomotion and ultrasonic communication). The same combination, however, promoted resilience against SI-induced immune changes, suggesting an alternative underlying mechanism than with i.p. poly(I:C) administration. Neither poly(I:C) nor SI had any effect on working or spatial memory, or sensorimotor gating. Therefore, despite producing some behavioural phenotypes with translational relevance to schizophrenia, further improvements and validation of the MIA and SI protocols are required to identify any benefit of or molecular mechanism involved in the ‘dual-hit’ model assessed in this thesis. Finally, the effects of SI on cortical gene expression were examined and interesting changes in genes associated with pathways including the circadian clock, mitogen-activated protein kinase (MAPK) signalling and dopaminergic neurotransmission were observed. These altered genes are discussed in the context of previous SI studies and their potential translational relevance to schizophrenia is considered.